EXCITING STUDENT CURIOSITY FOR A FUTURE CAREER: COVID-19 PANDEMIC ELECTIVE COURSE PROGRAM - Astuti, Triwahju; Duta, Garinda Alma (Universitas Gadjah Mada, 2023)
Background: Medical education disruptions as the impact of COVID-19 pandemic transform the way of Faculty of Medicine, Universitas Brawijaya conducted an elective clerkship program session.Aims: We consider evaluating the purpose and passion of 194 medical students that join the 2 weeks virtual Elective Course Program.Curriculum Discussion: Fifty-two tutors and 56 topics are involved. This integrates e-learning program divided into three Google Classrooms elective program. The survey at the end of program expressed the satisfaction of most of the students (59.7%). The online course programs also describe the future plan for the students. Seventy-one per cent students wish to continue specialization programs soon within a year after graduating and this interest is consistent and tends to grow after fifteen years from now.Conclusion: The enthusiasm to pursue a career seems has not been limited due to the COVID 19 Pandemic.